Microsphere‐Like SiO2/MXene Hybrid Material Enabling High Performance Anode for Lithium Ion Batteries. Issue 3 (23rd December 2019) - Mu, Ge; Mu, Daobin; Wu, Borong; Ma, Chengwei; Bi, Jiaying; Zhang, Ling; Yang, Hao; Wu, Feng
Abstract: To address the non‐negligible volume expansion and the inherent poor electronic conductivity of silica (SiO2 ) material, microsphere‐like SiO2 /MXene hybrid material is designed and successfully synthesized through the combination of the Stöber method and spray drying. The SiO2 nanoparticles are firmly anchored on the laminated MXene by the bonding effect, which boosts the structural stability during the long‐term cycling process. The MXene matrix not only possesses high elasticity to buffer the volume variation of SiO2 nanoparticles, but also promotes the transfer of electrons and lithium ions. Moreover, the microsphere wrapped with ductile MXene film reduces the specific surface area, relieves the side reactions, and enhances the coulombic efficiency. Therefore, superior electrochemical performance including high reversible capacity, outstanding cycle stability, high coulombic efficiency, especially in the first cycle, excellent rate capability as well as high areal capacity are acquired for SiO2 /MXene microspheres anode. Abstract : Microsphere‐like SiO2 /MXene hybrid material is designed and successfully synthesized through the combination of the Stöber method and spray drying. The bonding effect between SiO2 nanoparticles and MXene matrix boosts the structural stability of entire microspheres. The SiO2 /MXene anode enables high initial coulombic efficiency, high reversible capacity, superior cycling stability, and high areal capacity at high mass loading.